Teaching communication skills to students with severe disabilities - Downing, June (Paul H Brookes, 2015)
"This textbook is an essential guide for educators and other school-based staff to teach students with significant disabilities the necessary skills to communicate with those around them. This book shows readers how to analyze environments for their communicative value, assess students' communication skills, teach specific skills such as gaining attention and requesting, make informed choices about augmentative and alternative communication (AAC), and guide peers and adults in supporting students with disabilities"--